PENCEGAHAN PELECEHAN SEKSUAL SISWA SEKOLAH DASAR MELALUI IMPLEMENTASI PENDIDIKAN SEKSUAL MENURUT ISLAM - Ana Andriani; Tri Yuningsih (Universitas Muhammadiyah Purwokerto, 2023)
ABSTRACT Sexual violence often occurs in society, especially among elementary school students. This phenomenon is very worrying because it has an impact on their future. nowadays parents' activity is so busy, and it affects ignoring the important things that are vital for their children. Sexual violence is an unavoidable phenomenon. Uneducated television shows and an uncontrolled society are other factors. Parents' understanding of sexual education is still minimal because society is still considered taboo. As educators in schools, teachers can help provide an understanding of sexual education to students. So the knowledge needs of students are met, especially sexual education according to Islam. Educating and guiding students is the main task of the teacher. This study aims to determine the implementation of sexual education in elementary school students in Banyumas district. This research uses a qualitative approach with a case study method. Data collection techniques in this study are observation, interviews, and documentation. The results of the study show that the implementation of sexual education according to Islam has been carried out, among other things, by imposing a school curriculum that stipulates the students wear uniforms that cover the parts of the body that should go covered. Integrated into subjects such as Religion, Natural Sciences, Banyumasan Religion, and Culture is another proof. Media as a messenger used by teachers in sexual education according to Islam can be in the form of media pictures, posters, and introduction of songs about sexual education in children. Explanations about adab and morals are not only given by the teacher but also by other relevant elements.